2006 Global hunger index: a basis for cross-country comparisons - Wiesmann, Doris (International Food Policy Research Institute, 2006)
Indices can be powerful tools for international monitoring and advocacy, and if used in international rankings, can help foster a sense of healthy competition among countries. With this in mind, IFPRI’s Global Hunger Index (GHI) was designed to help mobilize political will and promote good policies by ranking countries and illustrating trends. It captures three dimensions of hunger: insufficient availability of food, shortfalls in the nutritional status of children, and child mortality, which is to a large extent attributable to undernutrition. Accordingly, the index includes the following three equally weighted indicators: the proportion of people who are food energy deficient as estimated by the Food and Agriculture Organization of the United Nations, the prevalence of underweight in children under the age of five as compiled by the World Health Organization, and the under-five mortality rate as reported by UNICEF